A novel deletion mutation in the DSG4 gene underlies autosomal recessive hypotrichosis with variable phenotype in two unrelated consanguineous families. (1st January 2015) - Ullah, A.; Raza, S. I.; Ali, R. H.; Naveed, A. K.; Jan, A.; Rizvi, S. D. A.; Satti, R.; Ahmad, W.
Summary: Background: Autosomal recessive hypotrichosis is a rare human hereditary disorder presenting as sparse scalp hair or as woolly hair occurring on various parts of the body. Various forms of isolated hypotrichosis have been reported to date. Mutations in at least 11 genes have been reported to cause hypotrichosis. Aims: To investigate the clinical and genetic basis of autosomal recessive hypotrichosis in two unrelated consanguineous families. Methods: Genotyping by highly polymorphic microsatellite markers established linkage in both families to the DSG4 gene on chromosome 18q21. PCR amplification of exons and intron–exon borders of the DSG4 gene was performed, and the products sequenced to search for disease‐causing sequence variants. Results: Clinical investigation revealed typical hypotrichosis in the affected members of one family, while other affected members showed presence of monilethrix‐like scalp hair. Sequence analysis of DSG4 revealed a novel deletion mutation (c.85‐1_191del) in the affected subjects of both families. Conclusions: This study further extends the body of evidence that mutations in the DSG4 gene result in both hypotrichosis and monilethrix‐like scalp hair.